Malignant Arrhythmias in Patients With COVID-19: Incidence, Mechanisms, and Outcomes. (November 2020) - Turagam, Mohit K.; Musikantow, Daniel; Goldman, Martin E.; Bassily-Marcus, Adel; Chu, Edward; Shivamurthy, Poojita; Lampert, Joshua; Kawamura, Iwanari; Bokhari, Mahmoud; Whang, William; Bier, Benjamin Aaron; Malick, Waqas; et al.
Abstract : Background: Patients with coronavirus disease 2019 (COVID-19) who develop cardiac injury are reported to experience higher rates of malignant cardiac arrhythmias. However, little is known about these arrhythmias—their frequency, the underlying mechanisms, and their impact on mortality. Methods: We extracted data from a registry (NCT04358029) regarding consecutive inpatients with confirmed COVID-19 who were receiving continuous telemetric ECG monitoring and had a definitive disposition of hospital discharge or death. Between patients who died versus discharged, we compared a primary composite end point of cardiac arrest from ventricular tachycardia/fibrillation or bradyarrhythmias such as atrioventricular block. Results: Among 800 patients with COVID-19 at Mount Sinai Hospital with definitive dispositions, 140 patients had telemetric monitoring, and either died (52) or were discharged (88). The median (interquartile range) age was 61 years (48–74); 73% men; and ethnicity was White in 34%. Comorbidities included hypertension in 61%, coronary artery disease in 25%, ventricular arrhythmia history in 1.4%, and no significant comorbidities in 16%. Compared with discharged patients, those who died had elevated peak troponin I levels (0.27 versus 0.02 ng/mL) and more primary end point events (17% versus 4%, P =0.01)—a difference driven by tachyarrhythmias. Fatal tachyarrhythmias invariably occurred in the presence of severe metabolic imbalance, while atrioventricular block was largely an independent primary event. Conclusions: Hospitalized patients with COVID-19 who die experience malignant cardiac arrhythmias more often than those surviving to discharge. However, these events represent a minority of cardiovascular deaths, and ventricular tachyarrhythmias are mainly associated with severe metabolic derangement. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04358029. Abstract : Supplemental Digital Content is available in the text.